Effects of end-stage renal disease and haemodialysis on dendritic cell subsets and basal and LPS-stimulated cytokine production - Sudhanshu Agrawal; P. Gollapudi; Reza Elahimehr; Madeleine V. Pahl; N.D. Vaziri (2009)
Background. Although bacterial infections have dramatically declined as a cause of death in the general population, they remain a major cause of mortality in patients with end-stage renal disease (ESRD). Moreover, the response to vaccination is profoundly impaired in this population. Dendritic cells (DC) are the major antigen-presenting cells that bridge the innate and adaptive immune responses. Activation of DC by pathogens results in secretion of inflammatory cytokines and up-regulation of co-stimulatory molecules. The activated DC prime naïve T and B cells to the captured antigens. Methods. Using flow cytometry, the number and phenotype of circulating DC [myeloid DC (mDC) and plasmacytoid DC (pDC)] were quantified in pre- and post-dialysis blood samples from 20 ESRD patients maintained on haemodialysis. Ten normal individuals served as controls. In addition, the level of DC activation and their response to lipopolysaccharide (LPS) stimulation were determined by assessing expression of co-stimulatory molecule, CD86, and antigen-presenting molecule, HLA-DR, as well as production of TNFα, IFNα and IL-6. Results. Compared to the control group, the circulating dendritic cell count was significantly reduced in the ESRD patients before dialysis and declined further after dialysis. The reduction in pDC numbers was more striking than mDC. The magnitude of the LPS-induced up-regulation of CD86 was comparable among the study groups as well as pre- and post-dialysis samples. However, LPS-induced TNFα production was significantly reduced in the post-dialysis samples with no significant difference in IL-6 and IFNα productions among the study groups and in pre- and post-dialysis samples. Conclusions. ESRD results in significant DC depletion which is largely due to diminished plasmacytoid DC subset. Haemodialysis procedure intensifies DC depletion and impairs LPS-induced TNFα production.